ABSOLUTE BIOAVAILABILITY OF ORAL MELOXICAM IN HEALTHY DOGS - K. T. Mahmood; M. Ashraf (Journal of Animal and Plant Sciences, 2010)
Meloxicam, a non-steroidal anti-Inflammatory drug has been registered in Pakistan as a safe substitute of diclofenac sodium which was banned for veterinary use, due to its relay toxicity associated with the catastrophic decline in vulture population of the Indian subcontinent. In Pakistan, Injection is the only dosage form registered for veterinary purposes whereas Boehringer Ingelheim  are licensed to sell meloxicam liquid oral suspension in UK and USA for use in dogs. The aim of the present study was to determine absolute bioavailability in dogs under local conditions of Pakistan. Eight dogs were used in two groups A & B (4x4) in a cross over fashion. The dogs in-group A were administered an intravenous bolus of meloxicam 0.2 mg.kg-1b.wt. and dogs in group B were administered an oral single dose of meloxicam 0.2 mg.kg-1b.wt.After wash out period of 14 days, experiment was repeated by change of treatment to group A and B. The blood samples were drawn at pre defined time intervals up to 96h. An HPLC method developed/validated at laboratories of UVAS/ LCWU, Lahore was used for the measurement of meloxicam concentration in plasma. The AUC (area under the curve) of all the dogs was determined from the plasma concentration versus time data following I/V and oral administration of the drug. The result indicated that the absolute bioavailability of meloxicam following oral administration at the dose of 0.2 mg.kg-1b.wt. was 90.24%. It is recommended that the oral dosage form like suspension must be developed / marketed in Pakistan in order to ensure easy administration of meloxicam at user end.
Keywords: Meloxicam; HPLC; absolute bioavailability; dogs